Mechanical and thermal properties of graphene and carbon nanotube reinforced epoxy/boron nitride adhesives. Issue 19 (2nd October 2021) - Wang, Shuo; Cao, Meng; Cong, Fanglin; Xue, Hongqian; Li, Xiaodong; Zhao, Changbao; Cui, Xu
Abstract: Outstanding mechanical properties and high thermal conductivity epoxy composites are being developed and are becoming urgent in the electronic and aerospace industries. Boron nitride nanosheet (BN), a nanomaterial with high thermal conductivity, and its epoxy composite adhesive have high thermal conductivity. However, due to its characteristics, the mechanical properties of BN/epoxy will decrease when more BN is added. Therefore, this study graphene platelet and carbon nanotube are selected and packed epoxy/BN composite adhesives to develop adhesives with excellent mechanical properties and thermal conductivity at the same time. In this study, an enhancement effect between a graphene platelet (GnP) and a carbon nanotube (CNT) within an epoxy/BN composite is reported. In the three-phase composite adhesive, the 2 D graphene platelets and 1D carbon nanotubes form a global bearing force network, and the boron nitride nanosheets provide high heat conduction inside the epoxy. They both complement each other in developing thermal conductive and high mechanical energy epoxy composite adhesives. At filler ranging from 0 to 1.0 wt%, epoxy/BN-CNT can improve the fracture toughness ( K 1c ), critical stress-energy release rate ( G 1c ) and Young's modulus of pure epoxy, are 89, 484, and 67% compared to 52, 286, and 42% in epoxy/BN-GnP composites, respectively. When adding 5.0 wt% of BN-CNT, the epoxy composites' thermal conductivity is up to 0.8 W/m%K, 400% higher than pure epoxy. This article also tested the electrical conductivity of epoxy/BN-CNT and epoxy/BN-GnP composites and found that the electrical conductivity was increased by 12 and 10 orders of magnitude, respectively, and it could be used as an antistatic material. Investigating the enhanced mechanism of epoxy/BN/CNT and epoxy/BN/GnP composites by scanning electron microscopy analysis. Lap shear strength tests on epoxy composite adhesives confirm the reinforcement effect of GnP and CNT of epoxy/BN composites. Graphical Abstract: UF0001